Solution of environmental problems through the media: case of kazakhstan: Solution of environmental problems through the media: case of kazakhstan - Zhurtbay, Nazym (Herald of Journalism, 2018)
Anders Hansen reminds us that:’Communication is central to how we come to know, and to know about, the environment and environmental issues, and the major communication media are a central public arena through which we become aware of environmental issues and the way they are addressed, contested and resolved’ (Hansen, 2011, p.9). Media (and Communication and Cultural) Studies research and teaching plays a central role in understanding how environmental issues are constructed, contested, understood and acted upon. Yet, the importance of mediated communication in understanding the environment appears not to be getting through to our students. One obvious answer is to explore the status of the environment as a topic of concern within the discipline – thus, we could turn around the question and ask, where is ‘the environment’ within Media Studies research? Hansen correctly claims that since the 1990s, and during the last decade in particular, environmental communication research has matured into an established field. However, it is still a relatively small subsection of Media and Communication Studies. This is evident when we take a brief look at the number of book publications on environment and media produced over the last 20 years.